2016
DOI: 10.1590/2317-4889201620160101
|View full text |Cite
|
Sign up to set email alerts
|

The Piriá aluminous lateritic profile: mineralogy, geochemistry and parent rock

Abstract: ABSTRACT:Relatively small aluminous lateritic deposits are abundant in the northeast and northwest parts of the Pará and Maranhão states, respectively. Most of them hosts aluminum phosphate mineralization forming hills and plateaus that stand out in the topography of the undulating plains of this region. The Piriá ridge is one of those topographic features, covered by lateritic iron crusts that have been studied in the 1970s as part of iron ore exploration campaigns and recently for phosphates prospection. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The positive correlation between Zr and REE indicates their preference for zircon. However, Ti is also positively correlated with REE, the same elements that correlates to Zr, suggesting that both zircon and anatase have accumulated together in the lateritic profile (Santos et al, 2016). The very similar distribution of Zr and SiO 2 in the SW portion of the LTI1 and the decrease in their concentrations towards the center of the lake are probably a function of hydraulic sorting of heavy minerals.…”
Section: Factor Controlling Distribution Of Inorganic Components In Smentioning
confidence: 84%
“…The positive correlation between Zr and REE indicates their preference for zircon. However, Ti is also positively correlated with REE, the same elements that correlates to Zr, suggesting that both zircon and anatase have accumulated together in the lateritic profile (Santos et al, 2016). The very similar distribution of Zr and SiO 2 in the SW portion of the LTI1 and the decrease in their concentrations towards the center of the lake are probably a function of hydraulic sorting of heavy minerals.…”
Section: Factor Controlling Distribution Of Inorganic Components In Smentioning
confidence: 84%
“…10B and anatase -Fig. 10F), which are insoluble and usually immobile under surface conditions (Jiang et al 2005, Santos et al 2016. Furthermore, the distribution curves of the chondrite normalized REE values show the geochemical signature of BIF (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The contribution of laterite weathering has been demonstrated by Costa (1991), Costa et al (2005a), Horbe and Costa (2005), Costa et al (2009), Costa et al (2011), Costa et al (2014), Santos et al (2016), Costa et al (2016), and Oliveira et al (2016). Also, these authors described the intense weathering due to the lateritization process and intense erosional activity in the ore deposits located in the Carajás and Amazon region.…”
Section: Introductionmentioning
confidence: 88%
“…The gibbsitic bauxites, essentially Tertiary or younger [6], are found mainly in a tropical region characterized by a hot and humid climate [3]. Diaspora has been found as a minor component in several types of bauxite in which it is accompanied by gibbsite and boehmite [28] suggested that diaspora is the stable phase under the surface under climatic conditions and that gibbsite and boehmite are metastable, the presence of which is largely due to slow transformations. Alumogoethite, found in many bauxite deposits, is a substitute for Fe in goethite and soil [29].…”
Section: Discussionmentioning
confidence: 99%